Differentially expressed tRFs in CD5 positive relapsed & refractory diffuse large B cell lymphoma and the bioinformatic analysis for their potential clinical use - Qingyuan Qu; Ying Li; Xiaosheng Fang; Lingyan Zhang; Chao Xue; Xueling Ge; Xin Wang; Yujie Jiang (Biology Direct, 2019)
Abstract Background Patients diagnosed as diffuse large B cell lymphoma (DLBCL) with CD5 positive normally have a worse outcome and poorly respond to the regulatory treatment strategy. Results We recently reported differently expressed tRFs and their potential target-genes of tRFs in patients with CD5+ R/R DLBCL. Differently expressed tRFs were detected by Illumina NextSeq instrument and the results were verified by quantitative real-time reverse transcription-PCR. tRF2Cancer database was searched to compared with the results. Further research was performed through bio-informatic analysis including gene ontology (GO) and pathway enrichment analyses, etc. A total of 308 tRFs were identified. Two sequences (AS-tDR-008946, AS-tDR-013492) were chosen for further investigated. Conclusions The results of Bioinformatics analysis revealed that the target genes including NEDD4L and UBA52 and several associated pathways including PI3K/AKT and MAPK/ERK might be involved in the development of CD5+ R/R DLBCL. Our preliminary study on the associated tRFs might provide a valuable measure to explore the pathogenesis and progression of CD5+ R/R DLBCL. Reviewers This article was reviewed by Zhen Qing Ye, Nagarajan Raju and Jin Zhuang Dou.